2011
DOI: 10.1111/j.1600-051x.2011.01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene, periodontal health and chronic obstructive pulmonary disease exacerbations

Abstract: Fewer remaining teeth, high PLI scores, and low tooth brushing times are significant correlates of COPD exacerbations, indicating that improving periodontal health and oral hygiene may be a potentially preventive strategy against COPD exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 45 publications
(81 reference statements)
7
105
1
5
Order By: Relevance
“…A case-control study from a hospital population in Beijing found that in analyses stratified for smoking there was no significant association between periodontitis and COPD (Wang et al 2009). Periodontal status was not associated with the frequency of exacerbations in patients with COPD (Liu et al 2012).…”
Section: Assessment Of Periodontitismentioning
confidence: 98%
“…A case-control study from a hospital population in Beijing found that in analyses stratified for smoking there was no significant association between periodontitis and COPD (Wang et al 2009). Periodontal status was not associated with the frequency of exacerbations in patients with COPD (Liu et al 2012).…”
Section: Assessment Of Periodontitismentioning
confidence: 98%
“…Probing depth, attachment loss, plaque index, alveolar bone loss and number of lost teeth were also positively correlated with the severity of COPD (3). In addition, a low quality of life, and poor oral hygiene or health status (such as a high number of lost teeth and a high plaque index) were significantly related to both CP and COPD (4,5).…”
Section: Introductionmentioning
confidence: 75%
“…Accordingly, the present study investigated the association between dental health and pulmonary function status after stratifying smoking experience and found that T-health index and ST were associated with pulmonary function status among non-smokers, while T-health index, ST, and MT were associated with pulmonary function status among smokers. In a study by Liu et al 9) that investigated exacerbation of COPD, oral hygiene, and periodontal health in subjects 30 years or older, exacerbation of COPD was greater when there were fewer natural teeth, plaque index was higher, and tooth brushing frequency was lower among non-smokers and former smokers. However, when smoking experience was stratified and confounding variables were adjusted, the present study did not find statistically significant differences in dental health and pulmonary function status between smokers and non-smokers.…”
Section: Fs-t Index Is Based On the Presumption That St Andmentioning
confidence: 99%
“…Moreover, it has also been reported that dental plaque that causes oral diseases contains about 100 million bacteria per 1 mm 2 of area and continuously supplies potential pathogens to the mouth and airways, which may enter the lungs through saliva and the upper respiratory tract 8) . There are also claims that COPD can be prevented by improving periodontal status and oral hygiene 9) . In Korea, a study analyzed data from the fourth Korea National Health and Nutrition Examination Survey (KNHANES) and reported that there was no association between periodontal disease and COPD 10) , while another analyzed data from the 2012 KNHANES to investigate the association between the number of natural teeth and COPD and found that having fewer natural teeth was associated with higher probability of COPD, but such association appeared only in males 11) .…”
Section: Introductionmentioning
confidence: 99%